Unraveling the Coulombic Efficiency Trough of Silicon Anodes in Li‐Ion Batteries - Asif Latief Bhat; Yu‐Sheng Su (Small Science)
The occurrence of Coulombic efficiency (CE) troughs in silicon (Si) anodes for lithium‐ion batteries (LIBs) presents a critical yet overlooked concern that can lead to battery failure in full cells. Herein, a comprehensive investigation into this previously unreported phenomenon is conducted. Factors influencing CE trough occurrence and severity, including electrode thickness, Si particle size, cycling rate, electrolyte composition, and voltage window, are systematically examined. Experimental results demonstrate that thinner electrodes and slower cycling rates accelerate CE trough onset, whereas employing a tetrahydrofuran (THF)‐based electrolyte or a narrower voltage window (0.01–0.5 V) results in stable electrochemical performance without CE troughs, concurrently with the presence of LixSi. Structural analysis via high‐angle annular dark‐field scanning transmission electron microscopy and scanning electron microscopy reveals a close association between CE trough severity, electrode volume expansion, and delamination, influenced by the formation of a sponge‐like structure and solid electrolyte interface (SEI) stability. These findings yield valuable insights into CE trough mechanisms and provide guidance for mitigating their occurrence through electrode design, electrolyte selection, and operational parameters, thereby advancing high‐performance LIB development. Future research directions involve exploring the role of SEI components and alternative electrolyte additives to enhance SEI stability and mitigate CE troughs.